A Systematic Review of Interventions to Address Accent-Related Communication Problems in Healthcare - Gu, Yulong (Ochsner J, 2019)
Background: Linguistic diversity in terms of speech, accent, and dialect can present a barrier to communication in healthcare. This review synthesizes current evidence on the effectiveness of interventions that target accent- or dialect-related communication problems in healthcare. Methods: Eligible studies were identified through a search of literature databases in 2018 using medical subject heading (MeSH) terms and additional keywords. Articles were screened for eligibility according to predetermined inclusion criteria. Because of the heterogeneity of the studies, effect data were analyzed using narrative synthesis. Results: Twenty-six studies (n=964) were included, reporting a range of interventions that provided accent modification training, role play or simulated patient consultation training, general language and consultation skills training, web-based training, and cultural competence training. Most studies (24 of the 26) indicated some benefits of the accent elements in the interventions based on objective or subjective measures. The key benefits were improvements in speech production, communication competence, and academic/clinical performance, as well as perceptual changes. Conclusion: Notwithstanding the low research quality and lack of standardized measures in the included studies, this review establishes an evidence base for implementing accent-related communication improvement strategies in healthcare. Large randomized controlled studies would be helpful to strengthen this evidence base.